Takhrij and Syarah Hadith of Chemistry: Content and Properties of Zam-zam water - Ihsan Ramadhan; Nurlia Putri Darani; Dede Suhendar; R Yuli Ahmad Hambali; Muhtar Solihin (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet Muhammad SAW. about benefits of zam-zam water. Qualitative research method uses the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this research is the hadith regarding the properties of zam-zam water, besides that there are also ingredients that can affect its properties. From this research is a authentic hadith and it can be proven the truth of the hadith, that zam-zam water is able to treat various types of diseases.